Implementation of the MBKM Program: Strengthening Student Literacy through a Kampus Mengajar Program - Nita Nyudiana; Rochman Hadi Mustofa (Didaktika: Jurnal Kependidikan, 2024)
The Kampus Mengajar program is a form of implementation of “Merdeka Belajar Kampus Merdeka”, which provides opportunities for students to apply the knowledge gained in higher education directly in the field. This study analyses the effectiveness of the literacy-strengthening program implemented at SDN Banyurip, Boyolali Regency. The method used is qualitative descriptive with a case study approach. Data were obtained through in-depth interviews and observations with resource persons. This study examines the programs implemented by Kampus Mengajar students to develop students' interest in reading and reading understanding related to literacy. The results of the study show that the literacy-strengthening program has had a positive impact on students. However, several challenges must be overcome by continuously implementing the program to achieve more optimal results.